Impact of Planting Density on the Effectiveness of Laboratory-Scale Artificial Wetlands Planted with Limonium Perezzi for Tannery Wastewater Treatment - Saenz-Reyes, Lina-Marcela; Agudelo-Valencia, Rafael-Nikolay; Ortiz-de-la-Hoz, Stivenzo-Rafael; Garcés-Polo, Siby-Inés (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The impact of the planting density of Limonium perezzi on the effectiveness of laboratory-scale artificial wetlands for the soaking stage wastewater treatment in tanneries was analyzed. The planting densities were 10.27 plants/m2 (HAP4) and 15.4 plants/m2 (HAP6). The hydraulic retention time in each wetland was 4.5 days, and the experiments were conducted for 32 days, when the plants began to wither and water samples were taken for the respective analysis. The wetlands were operated for 8 weeks to observe their deterioration with respect to time. The stabilization period of the wetlands varied between 7 and 10 days until the concentration of the effluent was little variable. The statistical analysis of the results indicates that the planting density influences the effectiveness of the wetland in terms of percentage of concentration decrease, the wetlands planted with 15.4 plants/m2 were more efficient, which was determined with the Student’s T test (p<0.05). The percentages of decrease in the chemical demand for oxygen, chlorides, and Total Dissolved Solids (TDS) for the highest planting density were 81%, 54%, and 55%, respectively. As in previous studies, it was observed that the planted species has the ability to absorb salt and release it through leaves and stems, as observed from the seventh day of operation.